CONCEPTS "MOTIVE", "MOTIVATION", "NEED AND MOTIVATIONAL SPHERE" IN SPORTS ACTIVITY (Academicia Globe: Inderscience Research, 2022)
This article discusses such concepts as "motive", "motivation", " need -motivational sphere" in sports activities. The main approaches to its study are revealed. The features of activity in sports are considered.